Pengaruh Variabel Makroekonomi Terhadap Stabilitas Perbankan Syariah dan Perbankan Konvensional Pada Periode Krisis dan Non-Krisis Di Indonesia - , MUH. FUAD ALAMSYAH; , Dr. Mamduh Mahmadah Hanafi, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The banking system in the country of Indonesia adheres Dual Banking System ( DSB ). The existence of the Dual Banking System ( DSB ) is due to Indonesia has two banking systems, namely Islamic banking and conventional. It is clearly a challenge for the central bank to regulate and supervise the banking system in Indonesia in accordance with UU No. 7 of 1992 which was revised into UU No. 10 of 1998 . Islamic economy is believed to provide a solution to build the Islamic financial system is more stable and secure because it is free from usury , maysir , and gharar that had been contained in the conventional financial system . This can be seen by many empirical studies that prove that the Islamic banking and financial system is more stable when compared to International conventional financial system. This study examined how much influence macroeconomic variables include inflation , unemployment , IHSG , balance of payments , exchange rate and interest rate stability BI on Islamic banking and conventional banking both in the crisis period (2008-2009) as well as in the non - crisis period ( 2011 â 2012 ) in Indonesia . The data used are quarterly data with an observation period of 2008. I - 2012. IV . By involving five ( 5 ) Islamic banks and five ( 5 ) existing conventional banks in Indonesia . The results of this study concluded that the macroeconomic variables affect the CAMEL Islamic banking in the whole period (2008.I-2012.IV). However, no impact on the crisis period (2008.I-2009.IV) and non-crisis (2011.I-2012.IV). In contrast to that experienced by conventional banks which are influenced by macroeconomic variables both in the overall period (2008.I-2012.IV) and the crisis period (2008.I-2009.IV) however, in the non-crisis period (2011.I -2012.IV) CAMEL conventional banks avoid volatility of macroeconomic variables. Furthermore, when tested using a variable interaction between macroeconomic variables (SBI and exchange rates) on a dummy variable (1 = syariah, 0 = conventional), it is clear that Islamic banking is more stable than conventional banks in the crisis period (2008.I- 2009.IV). However, in the non-crisis period (2011.I-2012.IV) performance of Islamic banking and conventional banking as good. Keywords : Islamic Banking, Conventional Banking, Macroeconomic variables